Development and Validation of a Screening Tool for The Identification of Refractive Errors Among School Going Children In Tamil Nadu, India - Sudharsan V; Prateeksha Dawn Davidson; Lakshmi Kandhan V; Amudha VP; Rita Hepsi Rani M (Medsci Publications, 2023)
Background: The inability to focus light onto the retina, known as refractive error, is a significant cause of correctable visual impairment. Unfortunately, students' ocular complaints often go unnoticed due to a lack of awareness. To address this issue, a questionnaire with high sensitivity and reasonable specificity was developed for teachers to identify students with refractive error. Methods: A questionnaire with surrogate indicators for refractive error in children was used and the data was analysed using SPSS. Significant markers were scored and a ROC curve determined a suitable cut-off. Sensitivity and specificity were calculated based on this cut-off. Results: The questionnaire was developed using five variables that had a 65% probability of identifying refractive error, including copying errors, copying from peers, eye squeezing, previous use of glasses, and eye deviation. A cut-off score of 5.5 out of 14 achieved 90% sensitivity and 50% specificity in detecting refractive errors. Conclusion: This study created a tool with five markers that demonstrated good internal consistency and content validity, it had an average sensitivity and specificity of 84% and 63%, respectively. The tool is twice as likely to identify someone with refractive error than someone without it.